THE ROLE OF GREEN SUKUK IN REALIZING A GOLDEN INDONESIA 2045 - Imron Natsir; Ahmad Abroza; Linda Ayu Oktoriza; Sulaiman Efendi Siregar; Rais Abdullah (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This study is a qualitative study with a descriptive approach that concerns the Role of Green Sukuk in Realizing Indonesia EMAS 2045. The data used in this study are secondary data that researchers obtained from Articles, Books, Credible Websites, and other things. The data used in this study were analyzed using the SWOT analysis tool. The result in this article show that the presence of Green Sukuk in realizing Indonesia EMAS 2045 has more strength because Indonesia has the largest Muslim population in the world, in terms of the environment and infrastructure development, Green Sukuk can be relied on, is more efficient, and has a longer term compared to other financial instruments. Keywords: Sun Tzu Strategy; Tourism Market; Tourism Village; Sustainable Tourism